Cancer patients diagnosed with COVID-19 infection: a multicenter retrospective cohort of nine Brazilian cancer centers - Monteiro, Mariana Ribeiro; Almeida, Kaique Ferreira Costa de; Abrahão, Ana Beatriz Kinupe; Souza, Camila Brambilla de; Carmo, Rafael Luis Moura Lima do; Andrade, Maria Clara Borges de; Freitas, Tuane Borges do Livramento; Longo, Cecilia Lameirinhas; Perdigão, Maria Carolina Lopes; Ferreira, Cynthia Lemos; Sousa, Tercia Tarciane Soares de; Maiolino, Angelo; Cruz, Sueli Monterroso da; Piotto, Gustavo Henrique Munhoz; Vieira, Fernando Meton de Alencar Camara; Araujo, Luiz Henrique (Brazilian Journal of Oncology, 2021)
Objectives: The COVID-19 infection was declared pandemic in March 2020. Since then, multiple studies have attempted to correlate clinical factors with the risk of complications from COVID-19. However, cancer patients are underrepresented in clinical trials and the results vary between different cohorts. Our goal is to describe a cohort of cancer patients and COVID-19. Methods: We conducted a multicenter retrospective study, based on a systematic review of medical records, including nine cancer centers, located in five different Brazilian cities. Patients were diagnosed with COVID-19 through RT-PCR between March 15th, 2020, and August 13th, 2020. Poisson regression models were then used to test for an association between clinical characteristics and severity of COVID-19 infections. Results: 102 patients had data collected for analysis, 85 (83.3%) of whom were hospitalized due to complications from COVID-19 infection. The median age was 65.8 years, most were female patients (61.8%) and white (73,5%). 78.4% had a performance status of 0-1, and the most common cancer subtypes were gastrointestinal (30.4%), breast (22.6%), and hematological (13.7%). Almost 40% of the population had stage IV disease. The mortality rate for all hospitalized patients was 36.5%, while that for those admitted to ICU was 68.4%. Key univariable risk factors for mortality included age (RR 1.03), ECOG = 2 (RR 1.83), hypertension (RR 1.72), lung metastasis (RR 1.67), and lymphocytes = 1000 admission (RR 2.40). At the multivariable analysis, the risk factors were also age (RR 1.02), primary lung cancer (RR 2.61), lung metastasis (RR 2.86), and coronary disease (RR 3.76). Conclusions: Despite the high mortality of patients hospitalized with COVID-19, cancer is a heterogeneous disease and some risk factors should be considered as the main responsible for the worst prognosis. Cancer patients should be carefully monitored in pandemic periods of infectious diseases and their management must be individualized.
Keywords: Coronavirus Infections; SARS Virus; Cancer Symptoms; Risk Factors; Clinical Evolution.